Adubação foliar com silicato na ocorrência de pragas e características agronômicas do feijoeiro comum - Alves, André Luiz (2016)
The objective of this study was to evaluate both the agronomic performance of two common bean cultivars and the population ocorrence of the main crop pests, according to foliar fertilization with potassium silicate. Experiments were conducted from August to December 2014 and from March to June 2015, under field conditions, in the rural area of Assis Chateaubriand, Paraná, Brazil. A randomized block design was used in both experiments, in a 2 x 5 factorial design, with four replications. The first factor refers to common bean cultivars (IPR Campos Gerais and IPR Tuiuiú), and the second factor refers to the doses of potassium silicate (0.0, 250, 500, 750 and 1000 ml ha-1). The product used contained 0.9 p.v. SiO2 (90 grams per liter of water) and 18% K2O in its formulation, and was diluted in humic acid. In both experiments, doses of potassium silicate were applied during phenological growth stages V3, V4 e R5, R6, R7 and R8 of crops by using the same quantity established for each treatment. The foliar fertilization with potassium silicate did not influence the agronomic characteristics of common bean cultivars, in both crops. IPR Campos Gerais cultivar presented plant height, thousand grain weight and grain yield higher than IPR Tuiuiú cultivar for rainy season crop. IPR Tuiuiú cultivar presented higher grain yield for dry season crop. Foliar fertilization with potassium silicate decreased populational ocorrence of crop pests belonging to Hemiptera, Lepidoptera and Coleoptera orders